Prediabetes Increases the Risk of Frailty in Prefrail Older Adults With Hypertension: Beneficial Effects of Metformin - Santulli, Gaetano; Visco, Valeria; Varzideh, Fahimeh; Guerra, Germano; Kansakar, Urna; Gasperi, Maurizio; Marro, Anna; Wilson, Scott; Ferrante, Mario Nicola Vittorio; Pansini, Antonella; Pirone, Armando; Di Lorenzo, Francesco; et al. (Hypertension (Dallas, Tex. 1979), 2024)
BACKGROUND: Prediabetes has garnered increasing attention due to its association with cardiovascular conditions, especially hypertension, which heightens the risk of prefrailty and frailty among older individuals. METHODS: We screened elders with prefrail hypertension from March 2021 to January 2023. We assessed the correlation linking cognitive dysfunction (Montreal Cognitive Assessment score), insulin resistance (triglyceride-to-glucose index), and physical impairment (5-meter gait speed). Then, we measured the risk of developing frailty after a 1-year follow-up period, adjusting the outcome using multivariable Cox regression analysis. We also investigated the impact of administering 500 mg of metformin once daily to a subset of frail subjects for an additional 6 months. RESULTS: We assessed the relationship between the triglyceride-to-glucose index and the Montreal Cognitive Assessment score, observing a significant correlation (r, 0.880; P<0.0001). Similarly, we analyzed the association between the triglyceride-to-glucose index and 5-meter gait speed, uncovering a significant link between insulin resistance and physical impairment (r, 0.809; P<0.0001). Prediabetes was found to significantly (P<0.0001) elevate the risk of frailty development compared with individuals without prediabetes by the end of the 1-year follow-up, a finding confirmed via multivariable analysis with Cox regression. Furthermore, among the subgroup of subjects who developed frailty, those who received metformin exhibited a significant decrease in frailty levels (P<0.0001). CONCLUSIONS: Insulin resistance and prediabetes play substantial roles in the development of cognitive and physical impairments, highlighting their importance in managing hypertension, even before the onset of frank diabetes. Metformin, a well-established drug for the treatment of diabetes, has shown favorable effects in mitigating frailty.